Gendering hatred: Adding ‘gender’ to the hate crime equation? - Gunthel, Natalie (Kvinder, Køn & Forskning, 2023)
Drawing on insights from human rights law, femicide laws, and hate crime studies, this article discusses the viability of including ‘gender’ in hate crime legislation, and the extent to which a legal approach of ‘gender-based hate crimes’ could serve a more effi cient response to the global prevalence of violence against women than similar types of legal measurements. The article argues that although there are sound principal reasons for including ‘gender’ in hate crime legislation, its inclusion is complicated by substantial conceptual and practical challenges, motivating instead a plethora of legal and non-legal approaches to counter and combat systemic violence against women.